Synthesis, physical and chemical properties of 7-methylxanthine derivatives - M. I. Romanenko; O. P. Dolhikh; D. H. Ivanchenko; K. V. Aleksandrova (Zaporozhye State Medical University, 2017)
It is known that 8-aminosubstituted N-methylated xanthines are dipeptidyl peptidase-4 antagonists, ligands for 5-hydroxytryptamine receptors and exert diverse biological effects. Previously, it was found that the 7-alkyl-8-piperazinoxanthines exhibit diuretic, depremic, analgesic effect. Some amino derivatives of 7-metilxanthine are promising antioxidants and 8-amino-7-ethyl-3-methylxanthine detects a distinct hypoglycemic effect. The aim of this work is to provide new derivatives of 7-methylxanthine - promising bioactive compounds and to study their physical and chemical properties as a basis for further structural modification of the molecule. Materials and methods. The melting point has been determined with the help of an open capillary method with PTP-M device. Elemental analysis has been performed with the help of the instrument Elementar Vario L cube, NMR-spectra have been taken on a spectrometer Bruker SF-400 (operating frequency of 400 MHz, solvent DMSO, internal standard - TMS). Results. It is established that the heating the source of bromxantine with an excess of primary amines in a mixture of water and dioxane leads to the formation of the corresponding 8-aminosubstituted 7-ethyl-3-methylxanthine. The reaction of 8-bromo-7-ethyl-3-methylxanthine and 8-bromo-7-ethyltheophylline with the more nucleophilic N-substituted piperazine is performed in the same conditions, but requires much less time and is accompanied by the formation of the corresponding 8-N-piperazinxanthines. Taking into account the amphoteric properties of imidazole it was possible to obtain 7-ethyl-8-(midazol-1)-3-methylxanthine through the reaction in dimethylformamide in the presence of equimolar amount of NaHCO3. 8-(4-Tret- butoxycarbonylaminopiperidinyl-1)-7-ethyl-3-methylxanthine and 8-(4-tret-butoxycarbonylamino-1)-7-ethyltheophylline are obtained by heating equimolar amounts of original bromxanthines, 4-tret-butoxycarbonylaminopiperidine and NaHCO3. The structure of the synthesized compounds is unambiguously proved by the method of NMR spectroscopy. The synthesized compounds are white crystalline substances soluble in hot alcohols, dioxane, DMF. The fact that 8-N,N-diethylamino-7-ethyl-3-methylxanthine and 7-ethyl-8-(midazol-1)-3-methylxanthine are well soluble in diluted acid solutions, can be used to obtain new bioactive salts with organic and inorganic acids. The presence of free N1H group enables the synthesis of new 1,3,7,8-tetrasubstituted of xanthine by the introduction of a variety of electrophilic reagents into the position of 1 uracil part of the molecule. Conclusions. Simply implemented methods for the synthesis of 8-amino-7-methylxanthine are developed. NMR-spectroscopic study of the obtained compounds, which clearly confirms their structure, is conducted. The prospective of the synthesized compounds for subsequent modification of their structure is demonstrated.